Une lecture méconnue de l'histoire : le service des cartes et plans aux Archives nationales (Culture et Communication, 1979)

Les archives nationales (France) en 1978 - Menier, Marie-Antoinette (La Gazette des archives, 1979)

L'association des archivistes français - Taillemite, Étienne (Gazette des archives, 1979)
Founded in 1904, this Association, which is now 75-year old, has a professional and technical status. It is dedicated to the study of all problems that may arise in the exercise of the archivist's profession, and the results of these studies have often had a decisive influence on the orientation of archival policy in France. It is rapidly expanding, just as the archivai profession itself.

Les archives et la documentation au niveau des administrations centrales - Chauleur, Andrée (La Gazette des archives, 1975)

L'Association des archivistes de l'Église de France - Duchein, Michel (Gazette des archives, 1974)

En marge des guides d'archives - Mariotte, Jean-Yves (Gazette des archives, 1974)

Manuel d'archivistique. Théorie et pratique des Archives publiques en France - Association des archivistes français (AAF) (1970)

Les archives françaises : organisation, législation, évolution - Duboscq, G. (Manuel d'archivistique. Théorie et pratique des Archives publiques en France, 1970)